Robust Manipulation of Magnetism in Dilute Magnetic Semiconductor (Ga, Mn)As by Organic Molecules. (5th November 2015) - Wang, Xiaolei; Wang, Hailong; Pan, Dong; Keiper, Timothy; Li, Lixia; Yu, Xuezhe; Lu, Jun; Lochner, Eric; von Molnár, Stephan; Xiong, Peng; Zhao, Jianhua
Abstract : Surface adsorption of organic molecules provides a new method for the robust manipulation of ferromagnetism in (Ga, Mn)As. Electron acceptor and donor molecules yield significant enhancement and suppression, respectively, of ferromagnetism with modulation of the Curie temperature spanning 36 K. Dip‐pen nanolithography is employed to directly pattern monolayers on (Ga, Mn)As, which is presented as a novel pathway toward producing magnetic nanostructures.